2002
DOI: 10.1211/002235702153
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive, vasodilator and antioxidant effects of a vinifera grape skin extract

Abstract: Cumulative evidence suggests that moderate wine consumption exerts a cardioprotective effect. We investigated the occurrence of an antihypertensive effect of an alcohol-free hydroalcoholic grape skin extract (GSE) obtained from skins of a vinifera grape (Vitis labrusca) in experimental rodent hypertension models. The vasodilator effect of GSE (polyphenols concentration 55.5 mg g(-1)) was also assessed in the isolated mesenteric vascular bed of Wistar rats and the antioxidant effect was studied on lipid peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…Grape extracts given orally reduced malondialdehyde content in rat heart, and might be resistant to myocardial ischemia reperfusion injury (Cui et al, 2002). Orally supplied alcohol-free hydroalcoholic grape skin extract from a vinifera grape, significantly reduced systolic and diastolic arterial pressure in chemically induced Wistar rat hypertension, as well as the decrease of lipid peroxidation (de Moura et al, 2002). The previous antihypertensive effect was seemed to be partly owing to antioxidant actions of grape seed extracts.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Grape extracts given orally reduced malondialdehyde content in rat heart, and might be resistant to myocardial ischemia reperfusion injury (Cui et al, 2002). Orally supplied alcohol-free hydroalcoholic grape skin extract from a vinifera grape, significantly reduced systolic and diastolic arterial pressure in chemically induced Wistar rat hypertension, as well as the decrease of lipid peroxidation (de Moura et al, 2002). The previous antihypertensive effect was seemed to be partly owing to antioxidant actions of grape seed extracts.…”
Section: Figurementioning
confidence: 99%
“…Recently, some researchers reported the physiological modification by polyphenolic compounds from grape, which include the cancer prevention (Bomser et al, 1999;Carbo et al, 1999;Zhao et al, 1999), the suppression of inflammation, the induction of vasorelaxation (Flesch et al, 1998), the decrease of blood pressure (de Moura et al, 2002), and so on. Resveratrol, the natural compound rich in red grapes, has the possibility of the phytoestrogenic action with the preventive or therapeutic effect for the hormonerelated diseases, because its similar structure to estrogen (Jang et al, 1997;Gehm et al, 1999;Lu and Serrero, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that chronic intake of the polyphenols contained in an alcohol-free lyophilized Brazilian red wine or in an alcohol-free grape skin extract (GSE) from Vitis labrusca reduced systolic, mean and diastolic arterial pressure in several experimental models of hypertension [16, 17]. Both types of extracts also caused endothelium-dependent vasodilation in the perfused rat mesenteric vascular bed by increasing the endothelial formation of both NO and EDHF [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of red wine consumption on coronary heart diseases might be attributable, at least in part, to polyphenols because non-alcoholic wine products and the purified polyphenols, quercetin and catechin, also prevented the progression of atherosclerotic lesions [16, 17]. In addition, oral intake of red wine polyphenols (RWPs) is able to prevent hypertension and endothelial dysfunction in several experimental models of hypertension, including chronic infusion of Ang II [18,19,20]. Recently, we have shown that RWPs strongly inhibit growth factor-induced expression of VEGF and MMP-2 in cultured vascular smooth muscle cells [21, 22].…”
Section: Introductionmentioning
confidence: 99%